Aleut baseball: Cultural creation and innovation through a sporting event - DeHass, Medeia; Droulias, Andreas (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
Aleut baseball is a popular game played by the Sugpiat of Nanwalek and Port Graham on the lower Kenai Peninsula of Alaska. Despite its resemblance to American baseball and Russian lapta, Aleut baseball should be considered a Sugpiaq cultural novelty. Ranging from recreational to competitive, the game is a communal occasion, which often brings together Sugpiaq villages and communities. This article presents some of the profound elements that make Aleut baseball expressive of Sugpiaq culture, and a channel for renegotiating and re-energising established norms and values. Furthermore, looking at Aleut baseball through Victor Turner’s concept of play, the authors argue that sports and games provide immense opportunities for cultural innovation and experimentation, as well as for strengthening of group identity. Finally, the article explores the capacity of sports and games to link global perceptions with local realities.